ADDITIONAL DANGEROUSITY: CRITERIA FOR PROFESSIONALS WHO WORK NEAR THE ELECTRIC POWER SYSTEM (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
Public lighting is a service connected to the electrical distribution system of the electric energyconcessionaires, which are active members of the electrical power system. The worker whoperforms the service and exposes himself to risk is the electrician. Some companies that providepublic lighting services do not pay the danger because they are unaware of the legitimacy of thecase or to avoid burdening the payroll. The objective of the present work is to evaluate if theseactivities are in fact dangerous, through a descriptive methodology with theoretical and legalbasis, involving laws, jurisprudence and doctrines on the right to the additional dangerousness forwork in the maintenance of the public lighting system. It is concluded that due to the exposureof the worker to the risks inherent to electricity, they live up to the perception of dangerousness.